Discourses for transformation? Climate change, power and pathways to the future - Carvalho, Anabela (2020)
Contemporary societies face various crises of sustainability related, inter alia, to consumption, resource use, financial management, employment, and environmental degradation. Climate change is the most threatening and wide-ranging expression of the environmental impact of human activity (especially as conducted in rich societies) in the last few decades. Since it emerged in policy and public arenas in the late 1980s, climate change has been assigned a variety of meanings with diverse implications for action. Discourses advanced by scientists, political actors, corporations, civic groups and others have been reconstructed in the media and other public fora in diverse ways, with values, worldviews and power issues working as important filters. Those aspects have also weighed heavily in the progressive institutionalization of discourses on climate change, which led to the dominance of techno-managerial approaches and the marginalization of calls for addressing structural issues at the root of climate change. In the USA and, to a smaller degree, in other societies, various economic and political forces have been continuingly invested in large-scale propaganda to deny scientific evidence and impede any changes to the present status quo.